ANALISIS KEBUTUHAN PENGEMBANGAN LEMBAR KERJA MURID BERBASIS MODEL PJBL-RAHMA TERINTEGRASI SDGS PADA MATERI SISTEM PENCERNAAN - Adiputri, Atika; Darussyamsu, Rahmawati; Zulyusri; Kurniati, Rahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the need for developing Student Worksheets (LKM) based on the PjBL-RAHMA model and integrated with the SDGs, specifically for the digestive system topic in Grade XI. A descriptive method was employed, utilizing interviews and questionnaires administered to two biology teachers and 32 students from class XI F2 at SMAN 15 Padang. The results indicate that the learning process remains teacher-centered, evidenced by the fact that 27.53% of students learn primarily by listening to teacher explanations. A total of 33.33% of students found the digestive system material difficult to comprehend, largely due to the abundance of confusing terminology and the complexity of the subject matter. Although 87.5% of students had previously used student worksheets and 96.87% found them helpful, the existing worksheets lacked integration with the SDGs; this is reflected in the finding that 68.75% of students had never heard of the SDGs, and 71.87% had never experienced SDG-integrated learning. The students expressed interest in PjBL-RAHMA-based worksheets integrated with the SDGs. These findings suggest that developing PjBL-RAHMA-based worksheets integrated with the SDGs is highly relevant for enhancing student engagement and conceptual understanding of the digestive system.